A quick-drying composite density gradient hydroentangled wiping cloth and a preparation method thereof

CN122899007APending Publication Date: 2026-10-13湖北欣柔卫生用品股份有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611098780.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

该方案属于化学交联改性中空纤维技术,不足之处在于化学改性工艺复杂,需要在碱性高温条件下进行化学反应,能耗高、存在环保问题,且端环氧聚醚类交联剂成本较高

Benefits of technology

1. 本发明通过特定的纤维配比与水刺工艺配合,在厚度方向上形成由两侧表层向中间芯层逐级递减的对称式阶梯密度梯度(上表层 0.25-0.35g/cm3、过渡层 0.18-0.24g/cm3、芯层 0.08-0.16g/cm3、下表层 0.25-0.35g/cm3)。这种结构使得高密度的上、下表层致密平滑,在接触晶圆、光学镜片等精密表面时摩擦力均匀,能有效防止掉屑并减少对基材的损伤;而低密度的芯层极为蓬松,结合30-50%中空度的粘胶纤维,形成了大量的三维储液微孔,使擦拭布的吸液率提升至580%以上,同时保持了良好的液体锁持能力,避免了擦拭过程中的液体回渗与二次污染。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a kind of quick-drying composite density gradient water-jet wiping cloth, including integrally water-jet forming, sequentially superimposed upper surface layer, transition layer, core layer and lower surface layer four-layer structure;The upper surface layer and lower surface layer are with solid PET staple as main fiber component, and the content of solid PET staple is 70-90% of the total mass of fiber of each layer respectively, and the balance is hollow viscose staple;The core layer is with hollow viscose staple as main fiber component, and the hollow degree of hollow viscose staple is 30-50%, and the content of hollow viscose staple in core layer is 60-80% of the total mass of fiber of core layer, and the balance is solid PET staple;The transition layer is located between upper surface layer and core layer, and the transition layer contains a mixture of solid PET staple, conductive PET staple and hollow viscose staple;The application completely avoids chemical modification route, and realizes directional liquid guiding through gradient structure, and the preparation method is integrally formed to avoid stratification, and the quick-drying performance is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of textile technology, specifically relating to a quick-drying composite density gradient spunlace wiping cloth and its preparation method. Background Technology

[0002] In cleaning operations involving optical lenses, precision electronic components, and medical equipment, wiping materials need to possess multiple properties simultaneously, including high liquid absorption rate, rapid drying, low lint shedding, and a soft touch.

[0003] In existing technologies, the following solutions are mainly adopted to achieve the above performance balance: CN107059243B discloses an antistatic viscose fiber nonwoven fabric and its preparation method. The method involves immersing viscose fibers in an antistatic treatment solution containing terminal epoxy polyethers, adjusting the pH to 10-11 with alkali, and then stirring at 85-100℃ to perform cross-linking modification, thereby obtaining a hollow structure in the fibers. This method belongs to chemical cross-linking modified hollow fiber technology. Its drawbacks include the complexity of the chemical modification process, requiring chemical reactions under alkaline and high-temperature conditions, resulting in high energy consumption, environmental issues, and the high cost of terminal epoxy polyether cross-linking agents.

[0004] CN119411374A discloses an antistatic, quick-drying cleanroom cloth, which is formed by spinning conductive PET and PA6 into a hollow fiber structure, followed by ultrasonic treatment with hydrochloric acid solution and low-temperature plasma treatment to obtain a porous hydrophilic structure. This method belongs to conductive hollow fiber spinning technology. Its shortcomings are that it requires multiple processes such as hydrochloric acid soaking, ultrasonic interval treatment, and plasma treatment, resulting in a long process flow. In addition, the hydrochloric acid treatment poses equipment corrosion and safety risks.

[0005] CN220363083U discloses a five-layer antistatic cleaning wipe, comprising a surface layer, an absorbent surface layer, an antibacterial layer, a base fabric layer, and a backing layer, with each layer joined by a heat-fused composite. This solution is a multi-layer composite structure, but its drawback is that the multi-layer composite structure increases the product's thickness and rigidity, and the heat-fused adhesive interfaces between the layers may delaminate during bending and friction, leading to lint shedding.

[0006] The common problems with existing technologies are: the chemically modified hollow fiber route is complex and energy-intensive; multi-layer composite structures have the risk of delamination; and conventional uniform hydroentangling processes cannot form the gradient pore structure required for directional liquid guidance within a single fabric. Summary of the Invention

[0007] To address the aforementioned issues, this invention provides a method for preparing a quick-drying composite density gradient spunlace wiping cloth that completely avoids chemical modification and achieves directional liquid guidance through a gradient structure. The preparation method involves integral molding to avoid delamination and exhibits excellent rapid drying performance.

[0008] To achieve the above objectives, the following technical solution is adopted: A quick-drying composite density gradient spunlace wiping cloth includes a four-layer structure consisting of an integrally spunlace molded upper surface layer, a transition layer, a core layer, and a lower surface layer stacked sequentially. Both the upper and lower layers are made of solid PET short fibers as the main fiber component, with the content of solid PET short fibers being 70-90% of the total fiber mass of each layer, and the remainder being hollow viscose short fibers. The core layer is mainly composed of hollow viscose staple fiber, with a hollowness of 30-50%. The content of hollow viscose staple fiber in the core layer is 60-80% of the total fiber mass of the core layer, and the remainder is solid PET staple fiber. The transition layer is located between the upper surface layer and the core layer. The transition layer contains a mixture of solid PET short fibers, conductive PET short fibers and hollow viscose short fibers. The content of conductive PET short fibers is 15-25% of the total mass of the transition layer fibers, the content of hollow viscose short fibers is 15-25%, and the remainder is solid PET short fibers. The wiping cloth has an upper surface layer density ρ1 of 0.25-0.35 g / cm³, a transition layer density ρ2 of 0.18-0.24 g / cm³, a core layer density ρ3 of 0.08-0.16 g / cm³, and a lower surface layer density ρ4 of 0.25-0.35 g / cm³. 3 And it satisfies the relationship ρ1>ρ2>ρ3, and the ratio of ρ1 / ρ3 is 2.5-3.5:1.

[0009] According to the above scheme, the conductive PET short fiber is a carbon black-filled conductive PET short fiber with a volume resistivity of 10³-10⁻¹⁰. 5 The fiber density is Ω·cm, the cut length is 38mm, and the fineness is 2.0 denier; in the transition layer, the mass ratio of conductive PET short fibers to hollow viscose short fibers is 1:0.8-1.2; the surface resistivity of the transition layer is 10 Ω·cm. 7 -10 10 Ω / sq.

[0010] According to the above scheme, the hollow viscose short fiber is a non-chemically cross-linked modified hollow viscose fiber. Its preparation process does not involve end-epoxy polyether cross-linking treatment, nor does it involve alkaline chemical modification steps at pH 10-11 and 85-100℃.

[0011] According to the above scheme, the cut length of the solid PET staple fiber is 38-51mm and the fineness is 1.0-2.0 denier; the cut length of the hollow viscose staple fiber is 30-45mm and the fineness is 1.5-2.5 denier.

[0012] According to the above scheme, the total surface density of the wiping cloth is 55-80 g / m², and the total thickness is 0.40-0.70 mm; the thickness ratio of the upper surface layer to the core layer is 1:1.5-2.5, and the thickness of the transition layer is 0.5-1.0 times the thickness of the upper surface layer.

[0013] According to the above scheme, the surface resistivity of the wiping cloth in the wet state is ≤1×10⁻⁶. 10 The surface resistivity in the wet state is ≤50% Ω / sq, and the change rate of the surface resistivity in the wet state compared with the dry state is ≤50%; the liquid absorption rate of the core layer is ≥580%, the drying time is ≤30min, and the test conditions are 25℃ and 50%RH.

[0014] According to the above scheme, the upper and / or lower surface layers also contain conductive PET short fibers accounting for 1-5% of the total mass of the fibers in their respective layers.

[0015] This invention also provides a method for preparing the above-mentioned quick-drying composite density gradient spunlace wiping cloth, comprising the following steps: S1. Fiber preparation: Prepare the upper surface fiber mixture, transition layer fiber mixture, core layer fiber mixture and lower surface fiber mixture respectively; S2, Four-layer fiber web laying: The above four fiber mixtures are respectively formed into four-layer fiber webs by carding and web forming process, and then laid into composite fiber webs in the order of upper surface layer-transition layer-core layer-lower surface layer; S3. Gradient Hydroentangling Reinforcement: The composite fiber web is conveyed to the hydroentangling equipment and reinforced using a four-stage variable pressure hydroentangling process; Stage 1: High-pressure hydroentangling at 100±5 bar is applied from the top layer of the composite fiber web. The high-pressure water jets penetrate the top layer and act on the transition layer, achieving densification of the top layer and moderate entanglement of the transition layer. The energy attenuation significantly weakens when it reaches the core layer, preserving the loose structure of the core layer; Stage 2: Medium-pressure hydroentangling at 80±5 bar is applied from the top layer of the composite fiber web to further strengthen the fiber entanglement of the transition layer, controlling the energy to prevent deep damage to the core layer pores; Stage 3: High-pressure hydroentangling at 100±5 bar is applied from the bottom layer of the composite fiber web to densify the bottom layer; Stage 4: Low-pressure hydroentangling at 40±5 bar is applied simultaneously from both sides of the composite fiber web to finish the fabric surface and consolidate surface loose fibers; The entire conveying speed is controlled at 18-22 m / min; S4. Dehydration and drying: Dehydrate the hydroentangled nonwoven fabric and dry it at 110-130℃. S5. Rolling: After cooling, trim the edges and roll up to obtain the finished product.

[0016] According to the above scheme, in step S3, the number of high-pressure water jets in the first and third sections are 3-4 each, with a water needle diameter of 0.12-0.15mm; the number of medium-pressure water jets in the second section is 2-3, and the pressure of each water jet is independently adjustable; the number of low-pressure water jets in the fourth section is 2-3 on each side.

[0017] This invention also provides the application of the above-mentioned quick-drying composite density gradient spunlace wiping cloth in the fields of precision device cleaning, optical lens wiping, semiconductor wafer cleaning, or medical device cleaning.

[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention, through a specific fiber ratio and hydroentangling process, forms a symmetrical stepped density gradient in the thickness direction, decreasing progressively from the outer two surface layers to the central core layer (0.25-0.35 g / cm³ on the upper surface). 3 Transition layer 0.18-0.24 g / cm³ 3 Core layer 0.08-0.16 g / cm³ 3 The lower surface layer has a concentration of 0.25-0.35 g / cm³. 3 This structure results in a dense and smooth upper and lower surface layer, providing uniform friction when in contact with precision surfaces such as wafers and optical lenses. This effectively prevents lint and reduces damage to the substrate. Meanwhile, the low-density core layer is extremely fluffy, combined with viscose fibers with a hollowness of 30-50%, forming numerous three-dimensional liquid-retaining micropores. This increases the liquid absorption rate of the wiping cloth to over 580%, while maintaining excellent liquid retention capabilities, preventing liquid backflow and secondary contamination during the wiping process.

[0019] 2. This invention features a transition layer containing 15-25% conductive PET short fibers, specifically designed between the surface layer and the core layer, and fixes this layer using a gradient hydroentangling process. On one hand, this transition layer forms a continuous conductive network, stabilizing the surface resistivity of the wiping cloth at 10 ppm. 7 -10 10 Within the Ω / sq range, and with a resistivity change rate ≤50% under wet conditions, it can quickly and stably discharge static electricity, meeting the electrostatic protection requirements of semiconductor manufacturing. On the other hand, by embedding conductive fibers in the intermediate transition layer, direct contact between them and the wiping surface is avoided. Combined with the design of a 1:0.8-1.2 mass ratio of conductive PET to hollow adhesive in the transition layer, the flexible buffering effect of the hollow adhesive effectively reduces the risk of surface scratches that may be caused by the hard conductive fibers in traditional blended wiping cloths.

[0020] 3. This invention explicitly limits the core layer to ordinary hollow viscose fiber that has not undergone end-epoxy polyether crosslinking treatment and high-temperature alkali modification, thus retaining the abundant active hydroxyl groups on the cellulose molecular chain, giving the wiping cloth excellent hydrophilicity and liquid absorption rate; at the same time, it avoids the introduction of chemical crosslinking agents or modifying agents, ensuring that the wiping cloth will not precipitate or swell when in contact with organic solvents, acid and alkali cleaning solutions or high-purity water, greatly improving the applicability of the product in fields such as semiconductors and medical devices where chemical purity requirements are extremely high.

[0021] 4. The preparation method of this invention abandons the traditional glue lamination or simple stacking process, and adopts a four-stage variable pressure hydroentangling technology of "high pressure-medium pressure-high pressure-double-sided low pressure". In particular, by using the medium pressure hydroentangling of 80±5 bar in the second stage, the entanglement degree of the transition layer is precisely controlled by utilizing the characteristic of hydroentangling energy decaying layer by layer. This ensures both appropriate entanglement of conductive fibers and effective control of water jet energy, preventing it from penetrating and damaging the loose structure of the core layer. This process achieves differentiated reinforcement and mechanical entanglement of fibers in each layer at a network speed of 18-22 m / min, which not only eliminates the risk of interlayer delamination, but also avoids chemical pollution caused by adhesives, ensuring the purity and structural stability of the product.

[0022] 5. By strictly controlling the drying temperature within the low-temperature range of 110-130℃, the risks of glass transition in PET fibers and heat damage to hollow viscose fibers are effectively avoided. This not only preserves the hollow structure and bulkiness of the core fibers, ensuring the long-term stability of high liquid absorption, but also maintains the integrity of the conductive pathways on the surface of the conductive fibers, enabling the product to maintain consistent performance under different temperature and humidity environments. Detailed Implementation

[0023] The following embodiments further illustrate the technical solution of the present invention, but are not intended to limit the scope of protection of the present invention.

[0024] Example 1 1. Raw material preparation; Top layer mixture: 88wt% solid PET staple fiber (specification: 1.5D×38mm) + 12wt% hollow viscose staple fiber (specification: 2.0D×38mm, hollowness 40%).

[0025] Transition layer mixture: 60wt% solid PET short fiber (1.5D×38mm) + 20wt% conductive PET short fiber (carbon black filled type, 2.0D×38mm, volume resistivity 10). 4 Ω·cm) + 20wt% hollow viscose staple fiber (2.0D×38mm, hollowness 40%).

[0026] Core layer mixture: 70wt% hollow viscose staple fiber (2.0D×38mm, 40% hollowness) + 30wt% solid PET staple fiber (1.5D×38mm).

[0027] Bottom layer mixture: 85wt% solid PET staple fiber (1.5D×38mm) + 15wt% hollow viscose staple fiber (2.0D×38mm, 40% hollowness).

[0028] 2. Four-layer fiber web laying: Four cross-laid carding machines are used to card the four types of fiber mixture into single webs, which are then stacked on the conveyor screen in the order of upper surface layer - transition layer - core layer - lower surface layer, forming a total basis weight of approximately 65 g / m². 2 Composite fiber web.

[0029] 3. Gradient hydroentangling reinforcement: The composite fiber web is fed into the hydroentangling unit, with the conveying speed set at 20m / min, using a four-stage variable pressure hydroentangling process. First stage (high pressure on the front): Water is sprayed from the upper surface of the composite fiber web at a pressure of 100 bar. Three water jet nozzles with a diameter of 0.13 mm are used. The high-pressure water jets penetrate the upper surface and act on the transition layer, achieving densification of the upper surface and initial entanglement of the transition layer. The energy is significantly reduced when it decays to the core layer, preserving the loose structure of the core layer. Second stage (frontal medium pressure): Continue to keep the fiber web orientation unchanged, still spray water from the top surface side, set the water pressure to 80 bar, use 2 water jet heads, water needle diameter 0.13 mm, further strengthen the fiber entanglement of the transition layer, and control the energy to prevent deep damage to the core layer pores. The third stage (high pressure on the reverse side): Flip the fiber web and spray water from the bottom surface side. Set the water pressure to 100 bar, use 3 water jet heads with a water jet diameter of 0.13 mm, and compact the bottom surface. The fourth stage (double-sided low-pressure finishing): water is sprayed on both sides simultaneously with a water pressure of 40 bar. Two water jets are used on each side to remove surface loose fibers and smooth the fabric surface.

[0030] 4. Dehydration and drying: After being dehydrated by vacuum dehydration rollers, the wet nonwoven fabric is placed in an oven for hot air penetration drying. The drying temperature is set at 120℃ to ensure that the physical properties of the fibers are not damaged while the moisture evaporates.

[0031] 5. Rolling and slitting: After drying, the fabric is cooled by cooling rollers, then trimmed and wound to finally produce a finished wiping cloth roll with a width of 1.2m.

[0032] The above-mentioned finished product was tested, and the results are as follows: Density test: ρ1 is 0.30 g / cm³. 3 The transition layer density ρ2 is 0.21 g / cm³. 3The core density ρ3 is 0.10 g / cm³. 3 The density ρ4 of the lower surface layer is 0.30 g / cm³. 3 And satisfying the relationship ρ1>ρ2>ρ3, with the ratio of ρ1 / ρ3 being 3:1. Antistatic performance: The resistivity of the dry surface is 6.8×10⁻⁶. 8 Ω / sq; Surface resistivity after wetting (deionized water) is 9.2×10⁻⁶. 8 Ω / sq, change rate 35.3%. Liquid absorption performance: core layer liquid absorption rate 628%, natural drying time at 25℃ and 50%RH is 26min. Appearance and feel: fabric surface is flat, no delamination, soft to the touch, no obvious stiffness.

[0033] Example 2 Raw material preparation: Top layer mixture: 90wt% solid PET short fibers (1.2D×38mm) + 10wt% hollow viscose short fibers (1.5D×38mm, 30% hollowness). Transition layer mixture: 70wt% solid PET short fibers (1.2D×38mm) + 15wt% conductive PET short fibers (carbon black filled type, 2.0D×38mm, volume resistivity 10). 5 Ω Core layer mixture: 80wt% hollow viscose short fibers (1.5D×38mm, 30% hollowness) + 20wt% solid PET short fibers (1.2D×38mm). Bottom layer mixture: 90wt% solid PET short fibers (1.2D×38mm) + 10wt% hollow viscose short fibers (1.5D×38mm, 30% hollowness).

[0034] The four-layer fiber web laying process is the same as in Example 1, and the total weight of the composite fiber web is approximately 55 g / m². 2 The gradient hydroentangling reinforcement conveyor speed was 22 m / min; the water pressure was 95 bar for the first stage, 75 bar for the second stage, 95 bar for the third stage, and 35 bar for the fourth stage; the number of hydroentangling heads and the diameter of the hydronephrite needles were the same as in Example 1. The dehydration and drying temperature was 115℃, and the rest were the same as in Example 1.

[0035] Density test: The density of the upper surface layer ρ1 = 0.27 g / cm³ 3 The density of the transition layer ρ2 = 0.19 g / cm³ 3 The core density ρ3 = 0.10 g / cm³ 3 The density of the lower surface layer ρ4 = 0.27 g / cm³ 3ρ1 / ρ3 = 2.7:1. Antistatic properties: The resistivity of the dry surface is 8.5 × 10⁻⁶. 9 Ω / sq; 1.2 × 10⁻⁶ after wetting 10 Ω / sq, change rate 41.2%. Liquid absorption performance: core layer liquid absorption rate 592%; natural drying time 24 min.

[0036] Example 3 Raw material preparation: Top layer mixture: 70wt% solid PET short fibers (2.0D×51mm) + 30wt% hollow viscose short fibers (2.5D×45mm, 50% hollowness). Transition layer mixture: 50wt% solid PET short fibers (2.0D×51mm) + 25wt% conductive PET short fibers (carbon black filled type, 2.0D×38mm, volume resistivity 10). 3 Ω Core layer mixture: 60wt% hollow viscose short fibers (2.5D×45mm, 50% hollowness) + 40wt% solid PET short fibers (2.0D×51mm). Bottom layer mixture: 70wt% solid PET short fibers (2.0D×51mm) + 30wt% hollow viscose short fibers (2.5D×45mm, 50% hollowness).

[0037] The four-layer fiber web laying process is the same as in Example 1, and the total basis weight of the composite fiber web is approximately 80 g / m². 2 The gradient hydroentangling reinforcement conveyor speed was 18 m / min; the water pressure was 105 bar for the first stage, 85 bar for the second stage, 105 bar for the third stage, and 45 bar for the fourth stage; the number of hydroentangling heads and the diameter of the hydronephrite needles were the same as in Example 1. The dehydration and drying temperature was 130℃, and the rest were the same as in Example 1.

[0038] Density test: The density of the upper surface layer ρ1 = 0.33 g / cm³ 3 The density of the transition layer is ρ2 = 0.23 g / cm³. 3 The core density ρ3 = 0.11 g / cm³ 3 The density of the lower surface layer ρ4 = 0.33 g / cm³ 3 ρ1 / ρ3 = 3.0:1. Antistatic properties: The resistivity of the dry surface is 3.2 × 10⁻⁶. 8 Ω / sq; 4.5 × 10⁻⁶ after wetting 8 Ω / sq, change rate 40.6%. Liquid absorption performance: core layer liquid absorption rate 675%; natural drying time 28 min.

[0039] Comparative Example 1 Repeat Example 1, but remove the transition layer structure and directly blend 20% conductive PET short fibers onto the upper surface layer. All other raw materials and process parameters are the same as in Example 1.

[0040] Test results: Resistivity of the dry surface: 5.6 × 10⁻⁶ 9 Ω / sq; 9.8 × 10⁻⁶ after wetting 9 Ω / sq, change rate 75% (significantly decreased wet stability). Surface hard fiber exposure points: 12 / 100cm. 2 (Example 1 is 0), there is a risk of scratches on the precision surface. Core layer liquid absorption rate: 572% (the high pressure on the surface layer directly damages the core layer's fluffiness, reducing its liquid absorption performance).

[0041] Comparative Example 2 Repeat Example 1, but adjust the pressure of the four hydroentanglement sections to 100 bar (uniform consolidation without gradient), while keeping the other parameters unchanged.

[0042] Test results: Density distribution: Top surface layer 0.28 g / cm³ 3 Core layer 0.24 g / cm 3 There was no obvious density gradient, ρ1 / ρ3 ≈ 1.17:1. Core layer liquid absorption rate: 428% (far lower than 628% in Example 1). Natural drying time: 42 min (beyond 30 min, quick-drying performance is lost). Dry shedding: 1.2 g / m³ 2 (Example 1: 0.6 g / m) 2 (The flaking performance deteriorates significantly).

[0043] Comparative Example 3 Repeat Example 1, except that the core layer hollow viscose is replaced with hollow viscose fiber modified by end-epoxy polyether crosslinking, while keeping all other parameters unchanged.

[0044] Test results: Core layer liquid absorption rate: 510% (chemical cross-linking blocks hydroxyl groups, reducing hydrophilicity). Small molecule precipitation after 48 hours of isopropanol immersion: 0.32 mg / m² (0.08 mg / m² in Example 1). 2 (The chemical purity is significantly reduced). Fiber swelling rate: 18% (7% in Example 1, indicating poor solvent resistance).

[0045] The relevant performance characterization data of Example 1 and Comparative Examples 1-3 are shown in Table 1.

[0046] Table 1 Based on the above embodiments and characterization data, this invention achieves a balance of multiple performance characteristics, including antistatic stability, high liquid absorption, quick drying, low scratch risk, and high chemical purity, through the synergistic design of "conductive fiber embedded in the transition layer + stepped density gradient + unmodified hollow adhesive". The absence of any core feature will lead to a significant deterioration of the corresponding performance, verifying the non-obviousness of the technical solution.

Claims

1. A quick-drying composite density gradient spunlace wiping cloth, characterized in that... It includes a four-layer structure consisting of an integral hydroentangled molding process, a top surface layer, a transition layer, a core layer, and a bottom surface layer stacked sequentially. Both the upper and lower layers are made of solid PET short fibers as the main fiber component, with the content of solid PET short fibers being 70-90% of the total fiber mass of each layer, and the remainder being hollow viscose short fibers. The core layer is mainly composed of hollow viscose staple fiber, with a hollowness of 30-50%. The content of hollow viscose staple fiber in the core layer is 60-80% of the total fiber mass of the core layer, and the remainder is solid PET staple fiber. The transition layer is located between the upper surface layer and the core layer. The transition layer contains a mixture of solid PET short fibers, conductive PET short fibers and hollow viscose short fibers. The content of conductive PET short fibers is 15-25% of the total mass of the transition layer fibers, the content of hollow viscose short fibers is 15-25%, and the remainder is solid PET short fibers. The wiping cloth has an upper surface layer density ρ1 of 0.25-0.35 g / cm³, a transition layer density ρ2 of 0.18-0.24 g / cm³, a core layer density ρ3 of 0.08-0.16 g / cm³, and a lower surface layer density ρ4 of 0.25-0.35 g / cm³. 3 And it satisfies the relationship ρ1>ρ2>ρ3, and the ratio of ρ1 / ρ3 is 2.5-3.5:

1.

2. The quick-drying composite density gradient spunlace wiping cloth as described in claim 1, characterized in that... The conductive PET short fiber is a carbon black-filled conductive PET short fiber with a volume resistivity of 10³-10⁻¹⁰. 5 The fiber density is Ω·cm, the cut length is 38mm, and the fineness is 2.0 denier; in the transition layer, the mass ratio of conductive PET short fibers to hollow viscose short fibers is 1:0.8-1.2; the surface resistivity of the transition layer is 10 Ω·cm. 7 -10 10 Ω / sq.

3. The quick-drying composite density gradient spunlace wiping cloth as described in claim 1, characterized in that... The hollow viscose staple fiber is a non-chemically cross-linked modified hollow viscose fiber.

4. The quick-drying composite density gradient spunlace wiping cloth as described in claim 1, characterized in that... The solid PET staple fiber has a cut length of 38-51 mm and a fineness of 1.0-2.0 denier; the hollow viscose staple fiber has a cut length of 30-45 mm and a fineness of 1.5-2.5 denier.

5. The quick-drying composite density gradient spunlace wiping cloth as described in claim 1, characterized in that... The total surface density of the wiping cloth is 55-80 g / m², and the total thickness is 0.40-0.70 mm; the thickness ratio of the upper surface layer to the core layer is 1:1.5-2.5, and the thickness of the transition layer is 0.5-1.0 times the thickness of the upper surface layer.

6. The quick-drying composite density gradient spunlace wiping cloth as described in claim 1, characterized in that... The surface resistivity of the wiping cloth in a wet state is ≤1×10⁻⁶. 10 The surface resistivity in the wet state is ≤50% Ω / sq, and the change rate of the surface resistivity in the wet state compared with the dry state is ≤50%; the liquid absorption rate of the core layer is ≥580%, the drying time is ≤30min, and the test conditions are 25℃ and 50%RH.

7. The quick-drying composite density gradient spunlace wiping cloth as described in claim 1, characterized in that... The upper and / or lower layers also contain conductive PET short fibers accounting for 1-5% of the total fiber mass of their respective layers.

8. The method for preparing the quick-drying composite density gradient spunlace wiping cloth according to any one of claims 1-7, characterized in that... Includes the following steps: S1. Fiber preparation: Prepare the upper surface fiber mixture, transition layer fiber mixture, core layer fiber mixture and lower surface fiber mixture respectively; S2, Four-layer fiber web laying: The above four fiber mixtures are respectively formed into four-layer fiber webs by carding and web forming process, and then laid into composite fiber webs in the order of upper surface layer-transition layer-core layer-lower surface layer; S3, Gradient hydroentanglement reinforcement: The composite fiber web is conveyed to the hydroentanglement equipment and reinforced using a four-stage variable pressure hydroentanglement process; The first stage involves applying 100±5 bar high-pressure hydroentangling from the top surface of the composite fiber web. The high-pressure water jets penetrate the top surface and act on the transition layer, achieving densification of the top surface and moderate entanglement of the transition layer. The energy decays significantly towards the core layer, preserving its loose structure. The second stage involves applying 80±5 bar medium-pressure hydroentangling from the top surface of the composite fiber web to further strengthen the fiber entanglement in the transition layer, controlling the energy to prevent deep damage to the core layer pores. The third stage involves applying 100±5 bar high-pressure hydroentangling from the bottom surface of the composite fiber web to densify the bottom surface. The fourth stage involves applying 40±5 bar low-pressure hydroentangling simultaneously from both sides of the composite fiber web to finish the fabric surface and solidify surface loose fibers. The entire web conveying speed is controlled at 18-22 m / min. S4. Dehydration and drying: Dehydrate the hydroentangled nonwoven fabric and dry it at 110-130℃. S5. Rolling: After cooling, trim the edges and roll up to obtain the finished product.

9. The method for preparing the quick-drying composite density gradient spunlace wiping cloth as described in claim 8, characterized in that... In step S3, the number of high-pressure water jets in the first and third sections are 3-4 each, with a water jet diameter of 0.12-0.15mm; the number of medium-pressure water jets in the second section is 2-3, and the pressure of each water jet is independently adjustable; the number of low-pressure water jets in the fourth section is 2-3 on each side.

10. The application of the quick-drying composite density gradient hydroentangled wiping cloth according to any one of claims 1-7 in the fields of precision device cleaning, optical lens wiping, semiconductor wafer cleaning or medical device cleaning.

Citation Information

Patent Citations

  • An antistatic viscose fiber nonwoven fabric and its preparation method

    CN107059243B

  • Antistatic quick-dry dust-free cloth and preparation method thereof

    CN119411374A